Some Results in Stability Analysis of Hybrid Dynamical Systems - Santos, I.L.D.; Silva, G.N. (Trends in Computational and Applied Mathematics, 2007)
In this paper we introduced a general model for the Hybrid Dynamical Systems and for such systems we introduced the usual concept of Lyapunov stability. Furthermore, we established two Principal Lyapunov Theorems and a converse theorem.